Physiological quality of maize seeds produced under soil water deficit conditions - Fernando H. B. Machado; Andréia M. S. de S. David; Silvânio R. dos Santos; Josiane C. Figueiredo; Cleisson D. da Silva; Danúbia A. C. Nobre (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Crop strategies focused on the rational use of water are required in semiarid regions. Thus, the objective of this work was to evaluate the physiological quality of maize seeds produced under soil water deficit conditions. Five irrigation water depth were established, based on the field capacity (100, 85, 70, 55 and 40%), to control the available water for two maize hybrids (2B-587 and DKB-390). A randomized block design was used, with a split-plot arrangement and four repetitions. The plots consisted of irrigation water depths, and the subplots consisted of maize hybrids. The seed water concentration, germination, and vigor were determined after the harvest, using data from first germination counting, seedling emergence, germination speed index, seedling length, and accelerated aging, electrical conductivity, and modified cold tests. The maize hybrid DKB-390 showed better physiological potential under the soil water deficit conditions evaluated. The irrigation water depths lower than 70% of field capacity resulted in decreases in soil water contents and affected negatively the physiological quality of the maize seeds produced.